Ritual Communication in Learning Islam in Multi-Religious School - Sauqi Futaqi; Ali Ahmad Yenuri (Universitas Muhammadiyah Yogyakarta, 2023)
Ritual practice is a basic feature in the religious life of a Muslim. Therefore, students in elementary schools are invited to practice religious rituals in learning the religion of Islam. Islamic Religious Education teachers try to teach students how to express their religion through rituals because ritual practice is a form of ritual communication. This study aims to describe and interpret the forms of religious rituals carried out in elementary schools, as well as communication models of religious rituals in building multicultural awareness. This study uses a qualitative-phenomenological approach. Data was collected by interviewing 18 informants in depth. Informants consisted of principals, religious teachers, parents and students. In addition, data were also obtained from several school documents. The research location is Setia Budhi Elementary School, East Java. Data analysis was carried out in three stages; data condensation, data display and conclusion drawing. The results showed that the communication of religious rituals that were expressed through Islamic Religious Education learning contained social messages from childhood. It can function as multicultural learning because the ritual communication is not only intended as a religious expression but as an expression of harmony and togetherness because they can cooperate with each other in celebrating their respective religious rituals. Although there is an exclusive side of a religion, such as prayer, fasting and others, in other rituals, they are able to communicate well, so that it contains learning content to respect each other.